2018
DOI: 10.3390/app8071071
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Seismic Behavior of Newly-Developed Precast Reinforced Concrete Block Masonry Shear Walls

Abstract: Typically, a special type of concrete block with cleaning holes is used in the bottom layer of traditional reinforced masonry shear walls (RMSWs) for mortar cleaning and vertical rebar connection, which results in reduced integrity and weakened structural behavior. In this paper, a precast construction technology was introduced to overcome these shortcomings. The cleaning-hole blocks were eliminated in the newly-developed precast RMSWs. Quasi-static tests on two traditional and two precast fully grouted RMSWs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
(27 reference statements)
1
13
0
1
Order By: Relevance
“…Steel plate shear wall is a kind of structure with high resistance to lateral force, which is suitable for the development of high-rise buildings [5][6][7][8]. Steel plate shear wall has been demonstrated with remarkable ability of seismic energy dissipation through the laboratory tests and aseismic implementations and have received much attention [9][10][11][12][13][14]. In 1994, Xue et al [15] found that the frame column should not only bear the vertical load but also bear the interlaminar shear force from the steel plate through the study of 4 trusses of steel plate shear walls with 3 spans and 12 floors.…”
Section: Introductionmentioning
confidence: 99%
“…Steel plate shear wall is a kind of structure with high resistance to lateral force, which is suitable for the development of high-rise buildings [5][6][7][8]. Steel plate shear wall has been demonstrated with remarkable ability of seismic energy dissipation through the laboratory tests and aseismic implementations and have received much attention [9][10][11][12][13][14]. In 1994, Xue et al [15] found that the frame column should not only bear the vertical load but also bear the interlaminar shear force from the steel plate through the study of 4 trusses of steel plate shear walls with 3 spans and 12 floors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the influence of the posttension duct cannot be ignored. Furthermore, studies on the seismic performance of reinforced concrete masonry structures concentrate on single-story walls [26][27][28][29], and little research has been carried out on collaborative work between two walls. Mavros et al [30] discussed shaking table tests on a full scale, two-story, reinforced masonry shear-wall structure, with two T-sectioned and one rectangular-section wall components.…”
Section: Introductionmentioning
confidence: 99%
“…Sejak zaman kuno pasangan bata sudah banyak digunakan sebagai bahan bangunan termasuk sebagian besar warisan arsitektur dunia menggunakan konstruksi bata (Oliveira et al, 2006). Blok beton mempunyai daya dukung yang tinggi sehingga struktur pasangan bata dapat mengurangi biaya konstruksi (Xu et al, 2018). Konstruksi bata menggunakan kombinasi bata dan mortar yang kekuatan tekannya juga bergantung pada lekatan keduanya (Vyas & Reddy, 2010).…”
Section: Pendahuluanunclassified